Trb3 controls mesenchymal stem cell lineage fate and enhances bone regeneration by scaffold-mediated local gene delivery. (January 2021) - Fan, Jiabing; Lee, Chung-Sung; Kim, Soyon; Zhang, Xiao; Pi-Anfruns, Joan; Guo, Mian; Chen, Chen; Rahnama, Matthew; Li, Jiong; Wu, Benjamin M.; Aghaloo, Tara L.; Lee, Min
Abstract: Aberrant lineage commitment of mesenchymal stem cells (MSCs) in marrow contributes to abnormal bone formation due to reduced osteogenic and increased adipogenic potency. While several major transcriptional factors associated with lineage differentiation have been found during the last few decades, the molecular switch for MSC fate determination and its role in skeletal regeneration remains largely unknown, limiting creation of effective therapeutic approaches. Tribbles homolog 3 (Trb3), a member of tribbles family pseudokinases, is known to exert diverse roles in cellular differentiation. Here, we investigated the reciprocal role of Trb3 in the regulation of osteogenic and adipogenic differentiation of MSCs in the context of bone formation, and examined the mechanisms by which Trb3 controls the adipo-osteogenic balance. Trb3 promoted osteoblastic commitment of MSCs at the expense of adipocyte differentiation. Mechanistically, Trb3 regulated cell-fate choice of MSCs through BMP/Smad and Wnt/β-catenin signals. Importantly, in vivo local delivery of Trb3 using a novel gelatin-conjugated caffeic acid-coated apatite/PLGA (GelCA-PLGA) scaffold stimulated robust bone regeneration and inhibited fat-filled cyst formation in rodent non-healing mandibular defect models. These findings demonstrate Trb3-based therapeutic strategies that favor osteoblastogenesis over adipogenesis for improved skeletal regeneration and future treatment of bone-loss disease. The distinctive approach implementing a scaffold-mediated local gene transfer may further broaden the translational use of targeting specific therapeutic gene related to lineage commitment for clinical bone treatment.